Research-Based Practice on the Implementation of a Brand Building Program in Higher Education: A Case Study - Vass, Vilmos (International Journal of Advanced Corporate Learning (iJAC), 2025)
The context of the paper is, on the one hand, growing trend of portfolio-based competency development in higher education, especially focusing on assessing students’ progression, promoting self-evaluation, reflective thinking, career planning, self-directed and collaborative learning strategies [1], [7], [17], [19]. Under the umbrella of portfolio-based higher education, brand building programs play important role in this process [5]. On the other hand, brand building programs can develop self-management skills at individual and system levels as well. At individual level, brand building promotes students in higher education to develop competencies, which are based on the labor market needs in order to reduce the skill gap and promote reskilling. At the organizational level, the paper focusing on the process from hierarchy to professional community. The first purpose of the paper is to introduce some results of the implementation of a 4-year MyBrand Program, especially focusing on the supporting system of the implementation. MyBrand Program in Budapest Metropolitan University is a careerfocused education initiative that focuses on practice-oriented education and the skills needed in the workplace promoting the successful future careers of students and successful placement in the labor market in the world of work. MyBrand program is linked to the University’s new, “creative university” identity. This paper introduces some parts of the program implementation: MyBrand portfolio workshops and trainings, Teachers’ Day and Club, mentoring program, basic competence matrix, MyBrand teaching handbook, METU Learn curricula, Online Knowledge Hub. The support system being developed is based on qualitative research on implementation of MyBrand Program, namely content analysis and 14 in-depth interviews. The second purpose of the paper is to give practical examples and students’ feedback of career planning at the course of Innovative learning technology skills in becoming an engineer at Óbuda University. At the conclusion part, I summarize on the results and experience of implementation of brand building program and the experience of career planning, tutoring and self-management in practice.